The changing meanings of diaspora : the Chinese in Southeast Asia - Liu, Hong (Routledge, 2019)
Dispersed over all corners of the earth, the Chinese diaspora -estimated to be around 60 million - is the largest in the world. It constitutes an important part of the Asian diaspora, not only because of its size, but also because three-quarters of the Chinese diaspora still reside in Southeast Asia today. Due to geographical proximity and trading ties, the Chinese diaspora has a long history in Southeast Asia, which was the main destination of emigrants from the Southern Chinese provinces of Fujian and Guangdong until the 1950s. From then onwards, remigration from Southeast Asia, Hong Kong and Taiwan to North America, Australasia, Europe and Japan led to a more geographically diverse Chinese diasporic landscape. Following the start of economic reforms in the People’s Republic of China (PRC) during the late 1970s, places of origin of Chinese emigrants also became more varied as the latter departed from all over China, and not merely from the traditional emigration areas (qiaoxiang) in South China. Even though the Chinese diaspora is unique in many ways, it can also illustrate some of the broader concerns and changing contexts pertaining to the Asian diaspora. These include questions of identity and homeland ties; the various factors that contribute to divisions within diasporas; the attempts of governments to incorporate diasporas; and the changing relationship between states and diasporas in different historical periods and geo-political contexts.